Improved Cumulative Survival in Fistulas Requiring Surgical Interventions to Promote Fistula Maturation Compared with Endovascular Interventions. Issue 1 (9th March 2012) - Lee, Timmy; Tindni, Arshdeep; Roy‐Chaudhury, Prabir
Abstract: Due to high nonmaturation rates, arteriovenous fistulas (AVF) frequently require intervention(s) to promote maturation. Endovascular or surgical interventions are often undertaken to salvage nonmaturing AVFs. The objective of this study was to compare the impact of surgical versus endovascular interventions to promote AVF maturation on cumulative AVF survival. We evaluated 89 patients with new AVF placement from a Veterans Affairs population over a 5‐year period. Of these, 46 (52%) required intervention(s) to achieve successful maturation for dialysis: 31 patients had surgical revisions and 15 patients had endovascular repairs. We compared cumulative survival between AVFs requiring no intervention, surgical revision, and endovascular intervention to promote AVF maturation. Cumulative survival was longer in AVFs receiving surgical intervention compared with angioplasty to promote AVF maturation ( p = 0.05). One‐year cumulative survival was 86% vs. 83% vs. 40% for no intervention vs. surgery vs. angioplasty, respectively. In AVFs that required interventions to promote maturation, AVFs with surgical intervention had longer cumulative survival compared with those AVFs with endovascular intervention. AVFs with surgical intervention to promote maturation had similar 1‐year cumulative survival to those AVFs that did not require intervention to promote maturation.